INCREASING THE STUDENTS’ VOCABULARY MASTERY USING REALIA - Ismita Trisani; Clarry Sada; Eni Rosnija (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research was conducted to answer the research question: “How effective is the use of realia to increase the vocabulary mastery of the third Grade Students of SDN 03 Pontianak Timur?” The method of this research is a Quasi-experimental Study. A Quasi- experimental Study requires one experimental group and one control group and needs the test namely Pretest and Posttest. The data is obtained from the writers’ observation for doing this research. The treatments were conducted in three-time meetings with the purpose to know the effectiveness of the teaching English language using realia to improving the students in vocabulary mastery. The population of this research was the third-grade students of SDN 03 Pontianak Timur. The population was 80 students of class 3A and Class 3B and all population were considered as sample of this research. The 40 students of class 3A as experimental group and the 40 students of class 3B as control group. The technique of data collecting was a multiple choice. The research findings showed that the result of computation on the t-test with 3.93 is higher than the t -table for the degree of freedom is 1.664. From the computation, it can be concluded that the teaching of vocabulary using realia is “highly effective”. Therefore, the null hypothesis that says “The use of Realia is not effective to increase the students’ vocabulary mastery” is rejected. And the alternative hypothesis that says “The use of Realia is effective to increase the students’ vocabulary mastery” is accepted.        Keywords: Increasing, Realia, Vocabulary, Young Learner.